Métodos de Redução de Picos em Sistemas OFDM Cooperativos Baseados na Técnica PTS - Teles, Lívia Christinie Sousa (2017)
This paper proposes a set of techniques for peak reduction in a cooperative OFDM system with AF relay and nonlinear PAs. The set of techniques are based on the PTS technique and they use PAPR and CM as metrics for choosing the transmitted signal. Both metrics are used to measure the amount of distortion introduced by PAs, so that minimizing them provides significant gains to the communication system. Numerical simulation results are presented to evaluate the performance of the set of proposed techniques.